2011
DOI: 10.1016/j.jcp.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and solution of multifrequency radiation diffusion equations for homogeneous refractive lossy media

Abstract: Starting from the radiation transport equation for homogeneous, refractive lossy media, we derive the corresponding time-dependent multifrequency diffusion equations. Zeroth and first moments of the transport equation couple the energy density, flux and pressure tensor. The system is closed by neglecting the temporal derivative of the flux and replacing the pressure tensor by its diagonal analogue. The system is coupled to a diffusion equation for the matter temperature. We are interested in modeling annealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For all but silica, the T increases more rapidly with power, which is consistent with both a decrease in k and a lack of significant radiation transport. 11,12 The data were well fitted with parameters A and as given in Table I. For silica, since the data in Fig.…”
Section: ͑2͒mentioning
confidence: 99%
“…For all but silica, the T increases more rapidly with power, which is consistent with both a decrease in k and a lack of significant radiation transport. 11,12 The data were well fitted with parameters A and as given in Table I. For silica, since the data in Fig.…”
Section: ͑2͒mentioning
confidence: 99%
“…Heat transfer boundary conditions for laser‐heating problems typically include surface convection, radiation, and evaporative cooling, but are highly dependent on the temperature range of interest. However, it can be shown that the large temperature gradients associated with laser heating of highly absorbing, low thermal diffusivity media result in radiative and convective loss from the surface that are negligible . Figure compares the relative contributions of the four transport mechanisms up to 3000 K, estimated analytically for a steady‐state 1 mm beam over a range of peak powers.…”
Section: Modelmentioning
confidence: 99%
“…However, it can be shown that the large temperature gradients associated with laser heating of highly absorbing, low thermal diffusivity media result in radiative and convective loss from the surface that are negligible. 35 Figure 2 compares the relative contributions of the four transport mechanisms up to 3000 K, estimated analytically for a steady-state 1 mm beam over a range of peak powers. As shown, until peak temperatures approach the boiling point of a-SiO 2 (2500 K), heat is lost largely through conductive cooling.…”
Section: Modelmentioning
confidence: 99%